Human rights in the peace and post-conflict policy in Colombia - Sonia Cortes Zambrano (Via Inveniendi Et Iudicandi, 2016)
Reflection falls on the costs of peace and post conflict in Colombia and concern for the realization or actual realization of human rights and attention to marginalized groups. This realization is made by the adoption of public policies with a rights perspective and with broad participation of civil society; thus, human rights become the reference point and ultimate goal for public policies on post-conflict and they turn on the instrument or suitable means for its realization. Thus, the focus of the rights of vulnerable populations must be a perspective to guide action and intervention by public authorities through the various plans and programs of economic and social development.